PENENTUAN MEKANISME PASAR EKONOM MUSLIM KLASIK - Putri Diesy Fitriani; Muhammad Husni Rijal (Masoem University, 2018)
Islamic Microeconomics is an economic study that discusses the behavior of individuals in carrying out their economic transactions with the norms applied with the limitations of the Qur'an and Sunnah. The understanding of the market is a place or condition that brings together demand with the bidder (buyer and seller) for each type of goods, services or resources. While the function is the relationship between variables one with other variables, with the change of a certain variable can be assessed and known in knowing and analyzing other variables. Equilibrium is a balance that occurs in a relatively long period of time and under certain conditions as a result of the intersection of demand and demand. As for the contributions of classical Muslim economists including the Al-Shahabah Risalat by Abdullah bin al-Muqaffa (109-145H / 727-762M) the contents include the administration of state finances, Al-Kharaj by Abu Yusuf (113-182H / 731-789M), Al -Kharaj is by Yahya bin Adam al-Qurasyi (140-203H / 757-818M), Al-Amwal by Abu Ubaid al-Qasim bin Sallam (157-224H / 774-838M), Al-Amwal by Abu Hamid bin Zanjawaih (180 -251H / 796-865M). Abu Yusuf's famous thoughts on the book Al-Kharaj also Al-Ghazali regarding the law of demand and supply.